New species and records of alpheid shrimps, genera Salmoneus Holthuis and Parabetaeus Coutière, from the tropical western Atlantic (Decapoda, Caridea) - Anker, Arthur (Zootaxa, 2007)
Six species of the alpheid shrimp genus Salmoneus Holthuis, 1955, including two new species, are reported from the tropical western Atlantic. Salmoneus ortmanni (Rankin, 1898) is reported for the first time from Atol das Rocas, Brazil and Aruba, Netherlands Antilles. Salmoneus carvachoi n. sp. is described on the basis of specimens previously misidentified as S. ortmanni from Guadeloupe, French Antilles, and is also known to occur in Brazil. The main difference between S. carvachoi n. sp. and S. ortmanni is the much more slender dactylus of the third to fifth pereiopods in the first species. The two species also appear to be ecologically separated: S. carvachoi n. sp. prefers silt-mud bottoms of estuaries and mangroves, while S. ortmanni occurs mostly in the rocky-coralline algae intertidal and on seagrass beds with reef patches, under rocks and coral rubble. Salmoneus rocas n. sp. is described on the basis of a single specimen collected at Atol das Rocas; this species belongs to the mostly Indo-Pacific S. serratidigitus (Coutière, 1896) species complex. Salmoneus teres Manning & Chace, 1990 and S. setosus Manning & Chace, 1990 previously known only from the isolated Ascension Island in the central Atlantic, are reported for the first time from the tropical western Atlantic: Guadeloupe and northeastern Brazil, respectively. Finally, Parabetaeus hummelincki (Schmitt, 1936) is recorded for the first time in Brazil.